The Link Between Parent–Child Relationship and Learning Engagement Among Adolescents: The Chain Mediating Roles of Learning Motivation and Academic Self-Efficacy - Shao, Yanhong; Kang, Shumin (Frontiers in Education, 2022)
Previous studies have indicated that parent-child relationship as well as learning motivation and academic self-efficacy is an influential factor of learning engagement, but the impact mechanism of the relevant factors needs to be explored. The purpose of the current study is to investigate how parent-child relationship is related to learning engagement via the mediating roles of learning motivation and academic self-efficacy. Structural equation modeling (SEM) was adopted for the analysis of 280 participants from China. Results showed that parent-child relationship was directly correlated with adolescents’ learning engagement. Results also showed that parent-child relationship indirectly predicted adolescents’ learning engagement via learning motivation and academic self-efficacy respectively and sequentially. More importantly, it was revealed that the direct effect was much lower than the total indirect effects which include the indirect effect of learning motivation, the indirect effect of academic self-efficacy, and the indirect effect of learning motivation and academic self-efficacy. Among the three indirect effects, the indirect effect of learning motivation and academic self-efficacy was the greatest. Major findings were discussed with implications and limitations in the study.